Application of Artificial Intelligence on Psychological Interventions and Diagnosis: An Overview - Zhou, Sijia; Zhao, Jingping; Zhang, Lulu (Frontiers in Psychiatry, 2022)
Background: Innovative technologies, such as machine learning, big data, and artificial intelligence (AI) are approaches adopted for personalized medicine, and psychological interventions and diagnosis are facing huge paradigm shifts. In this literature review, we aim to highlight potential applications of AI on psychological interventions and diagnosis. Methods: This literature review manifest studies that discuss how innovative technology as deep learning (DL) and AI is affecting psychological assessment and psychotherapy, we performed a search on PUBMED, and Web of Science using the terms ‘psychological interventions’, ‘diagnosis on mental health disorders’, ‘artificial intelligence’ and ‘deep learning’. Only studies considering patients’ datasets are considered. Results: Nine studies met the inclusion criteria. Beneficial effects on clinical symptoms or prediction were shown in these studies, but future study is needed to determine the long-term effects. Limitations: The major limitation for the current study is the small sample size, and lies in the lack of long-term follow-up-controlled studies for a certain symptom. Conclusions: AI such as DL applications showed promising results on clinical practice, which could lead to profound impact on personalized medicine for mental health conditions. Future studies can improve furthermore by increasing sample sizes and focusing on ethical approvals and adherence for online-therapy.